The advanced fixed income and derivatives management guide - Simozar, Saied, 1954- (Hoboken : Wiley, 2015)
"A highly-detailed, practical analysis of fixed income management The Advanced Fixed Income and Derivatives Management Guide provides a completely novel framework for analysis of fixed income securities and portfolio management, with over 700 useful equations. The most detailed analysis of inflation linked and corporate securities and bond options analysis available;, this book features numerous practical examples that can be used for creating alpha transfer to any fixed income portfolio. With a framework that unifies back office operations, such as risk management and portfolio management in a consistent way, readers will be able to better manage all sectors of fixed income, including bonds, mortgages, credits, and currencies, and their respective derivatives, including bond and interest rate futures and options, callable bonds, credit default swaps, interest rate swaps, swaptions and inflation swaps. Coverage includes never-before-seen detail on topics including recovery value, partial yields, arbitrage, and more, and the companion website features downloadable worksheets that can be used for measuring the risks of securities based on the term structure models. Many theoretical models of the TSIR lack the accuracy to be used by market practitioners, and the most popular models are not mathematically stable. This book helps readers develop stable and accurate TSIR for all fundamental rates, enabling analysis of even the most complex securities or cash flow structure. The components of the TSIR are almost identical to the modes of fluctuations of interest rates and represent the language with which the markets speak. Examine unique arbitrage, risk measurement, performance attribution, and replication of bond futures Learn to estimate recovery value from market data, and the impact of recovery value on risks Gain deeper insight into partial yields, product design, and portfolio construction Discover the proof that corporate bonds cannot follow efficient market hypothesis This useful guide provides a framework for systematic and consistent management of all global fixed income assets based on the term structure of rates. Practitioners seeking a more thorough management system will find solutions in The Advanced Fixed Income and Derivatives Management Guide"--
Machine generated contents note: List of Tables v List of Figures viii Abbreviations x Notation xii Preface xvii Acknowledgement xxi Foreword xxii Introduction 1 1. Review of Market Analytics 5 1.1. Bond Valuation 5 1.2. Simple Bond Analytics 7 1.3. Portfolio Analytics 9 1.4. Key Rate Durations 13 2. Term Structure of Rates 16 2.1. Linear and Non-linear Space 16 2.2. Basis Functions 18 2.3. Decay Coefficient 22 2.4. Forward Rates 22 2.5. Par Curve 24 2.6. Application to the US Yield Curve 24 2.7. Historical Yield Curve Components 27 2.8. Significance of the Term Structure Components 30 2.9. Estimating the Value of the Decay Coefficient 32 3. Comparison of Basis Functions 36 3.1. Polynomial Basis Functions 36 3.1. Exponential Basis Functions 36 3.1. Orthogonal Basis Functions 37 3.1. Key Basis Functions 38 3.5. Transformation of Basis Functions 40 3.3. Comparison with the Principal Components Analysis 47 3.4. Mean Reversion 53 3.5. Historical Tables of Basis Functions 55 4. Risk Measurement 57 4.1. Interest Rate Risks 57 4.2. Zero Coupon Bonds Examples 59 4.3. Eurodollar Futures Contracts Examples 61 4.4. Conventional Duration of a Portfolio 63 4.5. Risks and Basis Functions 64 4.6. Application to Key Rate Duration 67 4.7 Risk Measurement of a Treasury Index 72 5. Performance Attribution 74 5.1. Curve Performance 74 5.2. Yield Performance 76 5.3. Security Performance 76 5.4. Portfolio Performance 78 5.5. Aggregation of Contribution to Performance 84 6. Libor and Swaps 87 6.1. Term Structure of Libor 89 6.2. Adjustment Table for Rates 90 6.3. Risk Measurement and Performance Attribution of Swaps 92 6.4. Floating Libor Valuation and Risks 94 6.5. Repo and Financing Rate 97 6.6. Structural Problem of Swaps 97 7. Trading 100 7.1. Liquidity Management 100 7.2. Forward Pricing 104 7.3. Curve Trading 106 7.4. Synthetic Securities 111 7.5. Real Time Trading 115 8. Linear Optimization and Portfolio Replication 117 8.1. Portfolio Optimization Example 120 8.2. Conversion to and from Conventional KRD 123 8.3. KRD and Term Structure Hedging 124 9. Yield Volatility 125 9.1. Price Function of Yield Volatility 126 9.2. Term Structure of Yield Volatility 129 9.3. Volatility Adjustment Table 135 9.4. Forward and Instantaneous Volatility 137 10. Convexity and Long Rates 140 10.1. Theorem: Long Rates Can Never Change 140 10.2. Convexity Adjusted TSIR 144 10.3. Application to Convexity 149 10.4. Convexity Bias of Eurodollar Futures 154 11. Real Rates and Inflation Expectations 162 11.1. Term Structure of Real Rates 162 11.2. Theorem: Real Rates Cannot Have Log-normal Distribution 163 11.3. Inflation Linked (IL) Bonds 166 11.4. Seasonal Adjustments to Inflation 173 11.5. Inflation Swaps 179 12. Credit Spreads 184 12.1. Equilibrium Credit Spread 184 12.2. Term Structure of Credit Spreads 186 12.3. Risk Measurement of Credit Securities 187 12.4. Credit Risks Example 188 12.5. Floating Rate Credit Securities 189 12.6. TSCS Examples 191 12.7. Relative Values of Credit Securities 194 12.8. Performance Attribution of Credit Securities 197 12.9. Term Structure of Agencies 199 12.10. Performance Contribution 200 12.11. Partial Yield 203 13. Default and Recovery 206 13.1. Recovery, Guarantee and Default Probability 206 13.2. Risk Measurement with Recovery 211 13.3. Partial Yield of Complex Securities 218 13.4. Forward Coupon 220 13.5. Credit Default Swaps 221 14. Deliverable Bond Futures and Options 226 14.1. Simple Options Model 226 14.2. Conversion Factor 230 14.3. Futures Price on Delivery Date 231 14.4. Futures Price Prior to Delivery Date 231 14.5. Early versus Late Delivery 236 14.6. Strike Prices of the Underlying Options 237 14.7. Risk Measurement of Bond Futures 237 14.8. Analytics for Bond Futures 239 14.9. Australian Bond Futures 240 14.10. Replication of Bond Futures 241 14.11. Backtesting of Bond Futures 244 15. Bond Options 245 15.1. European Bond Options 245 15.2. Exercise Boundary of American Options 249 15.3. Present Value of a Future Bond Option 251 15.4. Feedforward Pricing 257 15.5. Bond Option Greeks 261 15.6. Risk Measurement of Bond Options 263 15.7. Treasury and Real Bonds Options 265 15.8. Bond Options with Credit Risk 266 15.9. Theorem: Credit Prices Are Not Arbitrage-free 269 15.10. Correlation Model 270 15.11. Credit Bond Options Examples 272 15.12. Risk Measurement of Complex Bond Options 274 15.13. Remarks on Bond Options 275 16. Currencies 277 16.1. Currency Forwards 278 16.2. Currency as an Asset Class 279 16.3. Currency Trading and Hedging 280 16.4. Valuation and Risks of Currency Positions 281 16.5. Currency Futures 283 16.6. Currency Options 283 17. Prepayment Model 285 17.1. Home Sale 285 17.2. Refinancing 287 17.3. Accelerated Payments 289 17.4. Prepayment Factor 290 18. Mortgage Bonds 291 18.1. Mortgage Valuation 292 18.2. Current Coupon 295 18.3. Mortgage Analytics 298 18.4. Mortgage Risk Measurement and Valuation 302 19. Product Design and Portfolio Construction 307 19.1. Product Analyzer 309 19.2. Portfolio Analyzer 312 19.3. Competitve Universe 313 19.4. Portfolio Construction 314 20. Calculating Parameters of the TSIR 319 20.1. Optimizing TSIR 321 20.2. Optimizing TSCR 325 20.3. Optimizing TSCR with No Convexity 329 20.4. Estimating Recovery Value 330 20.5. Robustness of the Term Structure Components 330 20.6. Calculating the Components of the TSYV 331 21. Implementation 333 21.1. Term Structure 333 21. 1.1. Primary Curve 333 21. 1.2. Real Curve 334 21. 1.3. Credit Curve and Recovery Value 335 21.2. Discount Function and Risk Measurement 336 21.3. Cash Flow Engine 337 21.4. Invoice Price 340 21.5. Analytics 340 21.6. Trade Date versus Settle Date 342 21.7. American Options 343 21.8. Linear Programming 348 21.9. Mortgage Analysis 349 References 351 Index 352.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Fixed-income securities; Derivative securities; Portfolio management; BUSINESS & ECONOMICS -- Finance; Derivative securities; Fixed-income securities; Portfolio management; BUSINESS & ECONOMICS / Finance; Electronic books